The Intersection Of Customary Law And National Land Law In The Settlement Of Land Disputes In Indonesia - Vincentius Raymond Wijaya (Sean Institute, 2024)
Customary land disputes in Indonesia reflect the complex relationship between customary law and state law, which often creates tensions and injustices for indigenous peoples. This research aims to explore the interaction between the two legal systems, with a focus on the recognition of indigenous peoples' customary rights in land dispute resolution. Legal Pluralism Theory is used as the main framework to analyze how customary law and formal law interact, collaborate, or clash. Data collected through interviews, legal documents, observations, and focus group discussions (FGDs) are analyzed to identify the challenges faced by indigenous peoples in obtaining their land rights. The results are expected to provide strategic recommendations on more inclusive and adaptive legal mechanisms, as well as customary land conflict resolution strategies based on distributive justice and social harmony. The research also emphasizes the importance of customary mediation as an alternative solution that is more responsive to local needs. By adopting a decentralized and participatory approach, this research will offer a more comprehensive picture of the dynamics of customary land conflicts in Indonesia, and strengthen the policy foundation to support social justice and the protection of indigenous peoples' rights.